Optimization of Strategy with SWOT Analysis to Increase Revenue of Imported Exterior Clothing Sales at Vn-Nee Collection Stores in Jayapura City - Girik Allo, Fenny (MultiTech Publisher, 2024)
The sustainability of small and medium-sized enterprises is critical in the face of the increasingly competitive challenges in this industry. The study aims to formulate a strategy for increasing the sales of imported used clothes in Vn-Nee Collection stores using the SWOT analysis approach. SWOT analytics is used to identify strengths, weaknesses, opportunities, and threats that affect VN-nee collection. The results of SWOT analyses indicate that Vn-nee Collection has significant internal strengths and is able to anticipate threats in the same business sector. Through a four-quadrant cartesius diagram approach. The implications of this finding are that the Vn-Nee Collection can leverage its internal strengths to design effective strategies for increasing competitive advantage, exploiting market opportunities, and managing risks emerging in this growing industry.